Synthesis of seawater based geopolymer: Characterization and adsorption capacity of methylene blue from wastewater. (2022) - Padmapriya, M.; Ramesh, S.T.; Biju, V.M.
Highlights: A mesoporous seawater-based geopolymer (SW-GP) was developed by using industrial by-products. The seawater-based geopolymer was synthesized at ambient temperature using seawater. A seawater-based geopolymer (SW-GP) is a promising adsorbent to remove methylene blue (MB) from aqueous solutions. The adsorption capacity of the seawater-based geopolymer was 59.52 mg/g. Abstract: The present work deals with a cost-effective removal of methylene blue (MB) dye utilizing a low-cost adsorbent, seawater based geopolymer (SW-GP) in the treatment of wastewater. It is prepared from different industrial by-products as raw materials such as coal fly ash (Class F), bottom ash (BA), and Ground Granulated Blast-furnace Slag (GGBS) by factorial mix design. The adsorbent was characterized using the Fourier-Transform Infra-Red spectroscopy (FT-IR) to identify the major functional groups. The percentage of elemental composition was calculated by X-ray fluorescence (XRF) analysis. The Scanning Electron Microscope (SEM) analysis confirms the presence of mullite and quartz in the adsorbent. The surface area was calculated by the Brunauer–Emmett–Teller (BET) analysis as 11.85 m 2 /g and pore size distribution was calculated by the Barrett–Joyner–Halenda (BJH) model to be 0.025 cm 3 /g. At an optimum dosage (0.08 g/L) of the geopolymer, the efficiency of MB color removal i.e. the adsorption capacity of the adsorbent was found as 81.36% and 59.52 mg/g respectively. Seawater based geopolymer (SW-GP) performs as an efficient adsorbent because of its less energy consumption in synthesis, larger surface area, and longer thermal stability up to 800°C for the removal of methylene blue in an aqueous medium by adsorption process.